Buddhist Vocabulary Learning Strategies of Graduate Students in Mahamakut Buddhist University - Phuangmali, Santirat; Puranaphatthanakul, Kitphisit; Klatngam, Sanya; Honghern, Phermpoon; Charoenwerakul, Sukanya (Journal of Dhamma for Life, 2025)
The objectives of this research were 1) to study the problems of Buddhist vocabulary learning of graduate students in Mahamakut Buddhist University, 2) to study Buddhist vocabulary learning strategies of graduate students in Mahamakut Buddhist University, 3) to present the model of Buddhist vocabulary learning strategies of graduate students in Mahamakut Buddhist University. The research methodology was a combination of quantitative and qualitative research. The sample group used was graduate students in Mahamakut Buddhist University, 50 persons. The research tools were questionnaires and interviews. Statistics used were frequency, percentage, mean, standard deviation. Data were analyzed by content analysis. The research results were found that: 1. The learning problem condition included Buddhist vocabulary is specialized vocabulary, teaching content emphasized memorization, lack of deep explanation of meaning, context and usage, some students lack effective vocabulary memorization skills, did not have motivation etc. 2. Graduate students' use of strategies for learning Buddhist vocabulary. Mahamakut Buddhist University Overall, it was at a high level ( = 3.47, S.D. = 0.76) 3. Model strategies for learning Buddhist vocabulary of graduate students at Mahamakut Buddhist University found that Creative thinking strategies helped stimulate thinking outside the box, encouraged learners to look at vocabulary from a new perspective, Participatory learning strategies encouraged interaction with one another, Memorization strategies helped to remember accurately, Cognitive strategies allow for deeper understanding.